O planejamento e controle da produção como ferramenta para melhoria da ecoeficiência: estudo de múltiplos casos em empresas fabricantes de embalagens plásticas - Costa, Itamar de Souza (2018)
In recent years, the organizations have been implementing the practice of eco-efficiency in the production system, in order to achieve economic and environmental gains. Eco-efficiency refers to strategies and measurements that allow companies to be environmentally responsible and profitable at the same time, consuming fewer natural resources, mitigating environmental impacts and consequently obtaining greater economic gains. In this context, the Production Planning and control (PPC), which is directly involved with production activities, may develop alternatives for companies to produce more, using fewer resources, explore renewable resources, recover, remanufacture and replace common raw materials with other biodegradable ones. Thus, this study aims to analyze the activities, the use of PPC’s tools, and their relationship with eco-efficiency in plastic packaging companies. The method adopted for this research, was multiple case study, through a structured interview. The result shows practical implications for the progress of the PPC's performance in industries, and the theoretical contributions in terms of directions for future research, regarding the relationship of PPC with eco-efficiency. The activities of recovery and reuse of chips and load sequencing, were the ones with greater prominence, as shown both in the literature and in practice, that is, in the researched case studies. Besides that, other findings such as the exchange of MTS system for MTO, preventive maintenance, SMED and the use of raw material of renewable products, were activities that, to a certain extent, showed relevance for the reduction of environmental impact in the companies of plastic packaging researched. Therefore, PPC is a tool that can help industrial managers to meet market demands while maintaining the competitiveness of their businesses, as well as promoting economic and environmental improvements. In this way, eco-efficiency occurs through the reduction of waste, the use of renewable raw materials, remanufacturing, recovery, reuse, adoption of good energy and water management in companies, among other activities or tools that assist the PPC in obtaining gains and environmental impact reduction.